Targeting ARID1A-mutant colorectal cancer: depletion of ARID1B increases radiosensitivity and modulates DNA damage response - Niedermaier, B. (Sci Rep, 2019)
The SWI/SNF chromatin remodeling complex has been found mutated in a wide range of human cancers, causing alterations in gene expression patterns, proliferation and DNA damage response that have been linked to poor clinical prognosis. Here, we investigated weather knockdown of ARID1B, one of two mutually exclusive subunits within the SWI/SNF complex, can sensitize colorectal cancer cell lines mutated in the other subunit, ARID1A, to ionizing radiation (IR). ARID1A-mutated colorectal cancer (CRC) cell lines are selectively sensitized to IR after siRNA mediated ARID1B depletion, as measured by clonogenic survival. This is characterized by a decrease in the surviving cell fraction to 87.3% ± 2.1%, 86.0% ± 1.1% and 77.2% ± 1.5% per 1 Gy compared with control siRNA exposed cells in the dose range of 0–6 Gy for the LS180, RKO and SW48 lines, respectively (p < 0.0001, F-test). The magnitude of this dose modifying effect was significantly larger in ARID1A mutated than in non-mutated cell lines (Spearman rank correlation rs = 0.88, p = 0.02). Furthermore, initial formation of RAD51 foci at 4 h after IR, as a measure for homologous recombination repair, was significantly reduced in ARID1A-mutant CRC cell lines but not in the majority of wildtype lines nor in fibroblasts. These findings open up perspectives for targeting ARID1B in combination with radiotherapy to improve outcomes of patients with ARID1A-mutant CRC.